Inherited unitals in Moulton planes - Korchmáros, Gábor (Ars mathematica contemporanea, 2018)
We prove that every Moulton plane of odd order-by duality every generalised André plane-contains a unital. We conjecture that such unitals are non-classical, that is, they are not isomorphic, as designs, to the Hermitian unital. We prove our conjecture for Moulton planes which differ from PG(2, q2) by a relatively small number of point-line incidences. Up to duality, our results extend previous analogous results-due to Barwick and Grünin-concerning inherited unitals in Hall planes.
Keywords: Hermitian; Moulton plane; Moultonova ravnina; Unital